2018
DOI: 10.1371/journal.pone.0201913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology and systematics of the cookiecutter sharks, genus Isistius Gill (1864) (Chondrichthyes: Squaliformes: Dalatiidae)

Abstract: The dalatiid genus Isistius Gill (1864) has three valid species currently recognized in the literature: Isistius brasiliensis Quoy & Gaimard (1824), I. plutodus Garrick & Springer (1964), and I. labialis Meng, Zhu & Li (1985). The most common species, I. brasiliensis, has a wide geographic distribution and is found in subtemperate and tropical seas circumglobally. A comparative analysis of specimens from different localities throughout its range, however, had never been undertaken. In the present paper, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 177 publications
0
22
0
Order By: Relevance
“…Taxonomic descriptions and museum collections may provide morphological data that may further reduce the number of animals sacrificed from field sampling. For example, taxonomists occasionally report measurements of mean or individual gill slit height in species descriptions ( El Kamel et al , 2009 ; Allen et al , 2016 ; de Figueiredo Petean and de Carvalho, 2018 ). Another possible data source for gill slit height and possibly other traits is preserved specimens or rare photos from museum collections.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic descriptions and museum collections may provide morphological data that may further reduce the number of animals sacrificed from field sampling. For example, taxonomists occasionally report measurements of mean or individual gill slit height in species descriptions ( El Kamel et al , 2009 ; Allen et al , 2016 ; de Figueiredo Petean and de Carvalho, 2018 ). Another possible data source for gill slit height and possibly other traits is preserved specimens or rare photos from museum collections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tail of D. licha, S. aliae, Z. squamulosus, T. kabeyai, and Etmopterus species, which is more mobile and brighter than the rest of the ventral surface area, could work as a distracting lure, and hence be analogous to the caudal photophores of myctophid and tubeshoulder fishes [115][116][117]. Conversely, the idea that the dark, photophore-free collar of I. brasiliensis acts as a lure to attract bigger pelagic fishes or marine mammals on which it feeds [51], now seems at the very least dubious given that numerous common preys of this shark species are either filter feeders or top predators for which such a mechanism is useless [65], and that the closely related species, the largetooth cookiecutter shark, I. plutodus, which has a similar diet [97], lacks such a collar [70].…”
Section: Ecology Of Shark Luminescencementioning
confidence: 99%
“…Currently, there are two recognized species of cookiecutter sharks, I. brasiliensis and I. plutodus (de Figueiredo Petean and R. de Carvalho ), and because Isistius bite wounds and scars tend to be either oval or round, it has been suggested that these shapes could be indicative of the biting species ( e.g ., Williams and Bunkley Williams , Pérez‐Zayas et al . ).…”
Section: Sightingsmentioning
confidence: 99%